The Phenomenon of Human Dignity in New Uzbekistan (International Journal of Scientific Trends, 2026)
This article analyzes the phenomenon of human dignity in New Uzbekistan within the framework of the social state concept. The new edition of the Constitution of the Republic of Uzbekistan, which officially recognizes the country as a social state, is considered as a solid legal foundation for ensuring human rights and freedoms. The article reveals the priority of the principle “human – society – state” in public policy, the improvement of the social protection system, the development of civil society institutions, and the essence of reforms aimed at enhancing human dignity. In addition, the philosophical and theoretical foundations of the social state are examined based on the views of Georg Wilhelm Friedrich Hegel and Jean-Jacques Rousseau. The results of the study show that ensuring human interests is a key priority in the process of building a social state.